CACAT QĀFIYAH DALAM PUISI UMRU’ AL-QAIS (KAJIAN PUISI PERSPEKTIF ILMU Al-QAWĀFI) - Patah, Akhmad; Ni'mah, Umi Nurun (Adabiyyāt: Jurnal Bahasa dan Sastra, 2022)
In general, the quality standard of classical Arabic poetry refers to the formulation of Al-Khalil bin Ahmad al-Farahidi, i.e Ilmu al-‘Arūd̩ wa al-Qawāfī. Even though these standards are so mainstream, in fact, some of the poetry of classical poets do not always live up to those standards, even the poetry of the great ones. This paper focuses on this, especially in terms of qāfiyah (rhymes of poetry), by taking the case of Umru' al-Qais poems as an example. The question that is then attempted to be answered is: how can a qualification be standardized when in fact, it is not fully followed by poets, even the great ones? The results of the discussion show that there are two possibilities. First, how the poets assessed the quality of poetry is different from how al-Farahidi did. Second, Al-Farahidi only took the abundant data available as what to be standardized in a theory.